Texts from the Swedish Courts - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Parallel texts downloaded from the websites of the Swedish Courts.
What was downloaded were pdf files. The txt files that are available are the result of running the pdf files through the pdftotext command from an ubuntu shell.

Parallella texter nedladdade från Domstolsverkets och Rättshjälpsmyndighetens webbplatser. Det som nedladdades var pdf-filer. De txt-filer som finns tillgängliga är resultat ur en körning av kommandot pdftotext i ubuntu-skal.
Texter från Domstolsverket/Rättshjälpsmyndigheten
Keywords: courts; domstolar; Legislation and legal systems; Lagstiftning och rättssystem; Crime and law enforcement; Kriminalitet och rättstillämpning; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Languages and Literature; Språk och litteratur; Other Legal Research; Annan rättsvetenskaplig forskning